2014
DOI: 10.1016/j.toxlet.2014.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Kidney biomarkers in MCPA-induced acute kidney injury in rats: Reduced clearance enhances early biomarker performance

Abstract: Accidental or intentional ingestion of glyphosate surfactant-based herbicides, like Roundup, leads to nephrotoxicity as well as death. In this study, a panel of kidney injury biomarkers was evaluated in terms of suitability to detect acute kidney injury and dysfunction. The Roundup intoxication model involved oral administration of glyphosate to rats at dose levels of 250, 500, 1200 and 2500 mg/kg. Urinary and plasma biomarker patterns were investigated at 8, 24 and 48 hours after dosing.Biomarkers were quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 58 publications
2
8
0
1
Order By: Relevance
“…In critically ill patients with AKI, OPN levels were high and correlated with RR in serial measurements, remarkably similar to our cohorts . In addition, OPN may be an earlier marker of AKI compared to other markers such as cystatin C . Its expression is up‐regulated in nephrons after acute injury and is associated with regeneration of renal tubular epithelia after acute tubular necrosis .…”
Section: Discussionsupporting
confidence: 83%
“…In critically ill patients with AKI, OPN levels were high and correlated with RR in serial measurements, remarkably similar to our cohorts . In addition, OPN may be an earlier marker of AKI compared to other markers such as cystatin C . Its expression is up‐regulated in nephrons after acute injury and is associated with regeneration of renal tubular epithelia after acute tubular necrosis .…”
Section: Discussionsupporting
confidence: 83%
“…KIM-1 has been shown to be a sensitive biomarker for the detection of various kidney injuries induced by drugs [42], toxins [43], and ischemia [44], as well as early stages of repair. Peng et al demonstrated that KIM-1 in rat expression was the most sensitive in urine compared with other ischemic acute kidney injury markers such as monocyte chemoattractant protein-l (MCP-1) and cystatin C (Cys C) [40].…”
Section: Discussionmentioning
confidence: 99%
“…Cisplatin, gentamicin, carbapenem, cyclosporine A, adriamycin, puromycin aminonucleoside, carboplatin, doxorubicin, bromoethylamine, paraquat [176], MCPA [177], glyphosate [178] Cisplatin [179], ifosfamide, methotrexate, gentamicin [175,180], contrast medium [181] β 2 -microglobulin Proximal tubular injury (reduced reabsorption); glomerular injury (leakage) Cadmium, cisplatin, puromycin aminonucleoside, carboplatin, gentamicin, cyclosporine, doxorubicin, bromoethylamine, contrast medium, paraquat [176], MCPA [177], glyphosate [178] Gentamicin and other aminoglycosides [172,182], vancomycin, contrast medium Gentamicin [180], cisplatin [179,183], contrast [185,186], paraquat poisoning [9] Interleukin-18 (IL-18)…”
Section: Figurementioning
confidence: 99%
“…Specific to proximal tubular injury; secreted in large quantities by dedifferentiated tubular cells Cisplatin, cyclosporine, gentamicin, cadmium, contrast medium, vancomycin carboplatin, doxorubicin, bromoethylamine, paraquat [176], MCPA [177], glyphosate [178] Paraquat poisoning [7], gentamicin [174,180], cisplatin [151,184] Neutrophil gelatinaseassociated lipocalin (NGAL)…”
Section: Contrast Medium Cisplatinmentioning
confidence: 99%
See 1 more Smart Citation